Bioconversion of Isoflavones into Bioactive Equol: State of the Art - B. Lopes, Danielle; R.A. de Avila, Amanda; D. de Queiros, Livia; A. Macedo, Juliana; A. Macedo, Gabriela (Recent Patents on Food, Nutrition & Agriculture, 2016)
Background: Soy isoflavones, an important class of phytoestrogens, are suggested to be responsible for a number of biological activities associated with health benefits, including defense against various chronic diseases, including breast and prostate cancer, cardiovascular disorders, and osteoporosis, and they may alleviate the symptoms of menopause. Methods: However, current researches (including patents) have shown that the clinical efficacy of these phenolic compounds is related to the ability of an individual to biotransform isoflavones into equol, which is a metabolite of daidzein formed exclusively by the intestinal microbiota. Results: This biologically active metabolite presents greater effects than other isoflavones; however, only about 30-50 % of people have a microbiota that is able to produce equol from dietary daidzein. Concern has recently grown about applications to improve the production of this metabolite. Conclusion: This paper summarizes the metabolism of equol, its production, and clinical implications.
Keywords: fecal microbiota